A new dawn for (oil) incumbents within the bioeconomy? Trade-offs and lessons for policy. (October 2020) - Hellsmark, Hans; Hansen, Teis
Abstract: This paper develops a more detailed understanding of when incumbent actors may become the main locomotive driving energy transitions. It also illustrates the trade-offs between policy approaches that actively seek to involve the incumbents in transitions, and policy approaches that pursue transitions without their active involvement. The paper examines state support for the bioeconomy in Sweden and concludes that public investments have been geared towards large-scale, complex and integrated biorefineries that are dependent on the active participation of the forest industry. Incumbents in the forest industry have, however, both lacked motivation and the abilities required to take the necessary steps for commercialisation of the demonstrated concepts. Instead, a rather small investment in a joint venture between actors from the forestry and oil refinery industry in Sweden has spurred learning and revenues; and it has placed an oil refinery at the centre of the future development of what we here term distributed biorefining. The main trade-off is that while this shift has opened up for cross-industrial collaborations and the production of advanced biofuels and materials, it has also paved the way for further investments in existing fossil-fuel infrastructure. Highlights: Low motivation of forest industry has stalled a transition to a bioeconomy. Public funding of forest biorefineries only payed-off when oil industry entered. Distributed biorefining enables the use of the oil refinery infrastructure. Motivation of forest industry has increased with the entry of the oil industry. Revenues from the bioeconomy can be used to revitalize the fossil economy.